Compound powder, molding, cured product, and method for producing compound powder
By controlling the particle size distribution of compound powders with large particles and a thermosetting resin, the issues of inadequate electrical insulation and aggregation in industrial applications are addressed, leading to improved performance and reduced defects.
Patent Information
- Application Number
- JP2024124415
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-03
AI Technical Summary
Conventional compound powders used in industrial products such as inductors and transformers suffer from inadequate electrical insulation and a tendency to aggregate, leading to issues like electrical short circuits and appearance defects.
The development of a compound powder with a controlled particle size distribution, comprising a high content of large particles (>500 μm) and a thermosetting resin, which improves electrical insulation and reduces aggregation.
The compound powder achieves enhanced electrical insulation and suppressed aggregation, resulting in improved performance and reduced defects in industrial products.
Smart Images

Figure 2025048740000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a compound powder, a molded body, a cured product, and a method for producing the compound powder. [Background technology]
[0002] Compound powders containing soft magnetic metal powders and insulating resin compositions are used as raw materials for various industrial products (see Patent Document 1 below). For example, compound powders are used as raw materials for inductors, transformers, reactors, thyristor valves, noise filters (EMI filters), choke coils, motor cores, rotors and yokes of motors used in general household appliances and industrial equipment, electromagnetic shields, and solenoid cores (fixed cores) for solenoid valves. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-277374 A Summary of the Invention [Problem to be solved by the invention]
[0004] The metal powder contained in the compound powder has not only soft magnetic properties (relatively high relative permeability and relatively low coercive force) but also electrical conductivity. Therefore, conventional compound powders do not have sufficient electrical insulation properties (voltage resistance, etc.). As the content of metal powder in the compound powder increases, the soft magnetic properties of the compound powder improve, but the electrical insulation properties of the compound powder deteriorate. Compound powders with poor electrical insulation properties cause electrical short circuits and eddy current losses in the industrial products described above.
[0005] Furthermore, the metal powder is easily separated from the resin composition. Due to the separation of the metal powder and the resin composition, blocking (agglomeration) of the compound powder is easily caused. Blocking of the compound powder impairs the fluidity of the compound powder, causing appearance defects of industrial products manufactured by molding the compound powder. For example, due to blocking of the compound powder accompanying transfer molding or compression molding of the compound powder, appearance defects such as flow marks and whitish haze or white marks are easily generated on the surface of the hardened product of the compound powder.
[0006] At least some of the particles constituting the compound powder are composite particles composed of at least one metal particle constituting the metal powder and a resin composition covering the metal particle, and the electrical insulation of the compound powder is derived from the resin composition covering the metal particle. Therefore, as the resin composition covering the metal particle increases, the particle size of each composite particle (the thickness of the resin composition covering the metal particle) increases, and the electrical insulation of each composite particle itself improves. In other words, as the resin composition covering the metal particle decreases, the particle size of the composite particle decreases, and the electrical insulation of each composite particle itself deteriorates. Furthermore, the smaller the particle size of the metal particle, the easier the resin composition peels off from the surface of the metal particle. Therefore, it is expected that the electrical insulation of the compound powder will be improved by removing particles with a relatively small particle size from the compound powder.
[0007] Furthermore, as the particle size of each particle constituting the compound powder decreases, the specific surface area of each particle increases, and the particles tend to come into contact with each other and aggregate. In other words, the smaller the particles constituting the compound powder, the more likely blocking (aggregation) of the compound powder occurs. Therefore, it is expected that blocking of the compound powder can be suppressed by removing particles with relatively small particle sizes from the compound powder.
[0008] Based on the above considerations, the inventors focused on the particle size distribution of the compound powder and came up with the present invention, which improves the electrical insulation of the compound powder and suppresses blocking of the compound powder by controlling the particle size distribution of the compound powder.
[0009] An object of one aspect of the present invention is to provide a compound powder having excellent electrical insulation properties (voltage resistance) and suppressed blocking (aggregation), a molded body containing the compound powder, a cured product of the compound powder, and a method for producing the compound powder. [Means for solving the problem]
[0010] For example, one aspect of the present invention relates to the following [1] to
[10] .
[0011] [1] A compound powder comprising a metal powder and a resin composition, The metal powder is a soft magnetic material. The resin composition includes a thermosetting resin, The compound powder contains a plurality of large particles having a particle size of more than 500 μm. The content of large particles in the compound powder is 40% by mass or more and 100% by mass or less. Compound powder.
[0012] [2] At least some of the large particles are At least one metal particle constituting a metal powder; A resin composition that covers metal particles; Including, [1] Compound powder described in the above.
[0013] [3] The minimum melt viscosity of the compound powder at 175°C is greater than or equal to 10 Pa·s and less than or equal to 250 Pa·s; [1] or [2].
[0014] [4] The content of metal powder in the compound powder is 94% by mass or more and 98% by mass or less; A compound powder according to any one of [1] to [3].
[0015] [5] The resin composition further contains at least one component selected from the group consisting of a curing agent, a curing accelerator, a coupling agent, and a wax. [1] - [4] The compound powder according to any one of the above.
[0016] [6] Used in the magnetic core of a coil, [1] - [5] The compound powder according to any one of the above. [1] to [5], wherein the compound powder is used for a magnetic core of a coil.
[0017] [7] An encapsulant, [1] - [5] The compound powder according to any one of the above. [1] to [5], wherein the compound powder is used as a sealing material.
[0018] [8] A molded body comprising the compound powder according to any one of [1] to [7].
[0019] [9] A hardened product of the compound powder described in any one of [1] to [7].
[0020]
[10] A method for producing a compound powder according to any one of [1] to [7], A step of preparing a mixed powder containing a metal powder and a resin composition; obtaining a compound powder containing a plurality of large particles by classifying the mixed powder; Including, Manufacturing method of compound powder. Effect of the Invention
[0021] According to one aspect of the present invention, there are provided a compound powder having excellent electrical insulation (voltage resistance) and suppressed blocking (aggregation), a molded body containing the compound powder, a cured product of the compound powder, and a method for producing the compound powder. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view of a compound powder according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. In the drawings, the same components are designated by the same reference numerals. The present invention is not limited to the following embodiments.
[0024] (Compound powder, molded body, and hardened material) As shown in FIG. 1, the compound powder 10 according to the present embodiment is a powder at room temperature (for example, (20±15)° C.). The compound powder 10 includes a metal powder and a resin composition 3. The metal powder is composed of a plurality of metal particles 1. The metal powder is a soft magnetic material. The metal powder may be referred to as a metal filler. The resin composition 3 includes a thermosetting resin. The resin composition 3 has electrical insulation properties. The compound powder 10 may include one or both of an uncured product of the resin composition 3 and a semi-cured product of the resin composition 3 (B-stage resin composition 3). In a molded product including the compound powder 10 or a cured product of the compound powder 10, the resin composition 3 bonds the plurality of metal particles 1 to each other. Furthermore, the resin composition 3 interposed between the plurality of adjacent metal particles 1 electrically insulates the plurality of metal particles 1. The compound powder 10 may be composed of only the metal powder and the resin composition 3. The compound powder 10 may further contain other components in addition to the metal powder and the resin composition 3 .
[0025] The molded body according to this embodiment includes the above-mentioned compound powder 10. The molded body according to this embodiment may consist of only the compound powder 10. The molded body may include other members such as a coil in addition to the compound powder 10. The molded body may include one or both of an uncured product of the resin composition 3 and a semi-cured product of the resin composition 3. The cured product according to this embodiment is a cured product of the above-mentioned compound powder 10, and includes a cured product of the resin composition 3 (C-stage resin composition 3). The electrical insulation properties (e.g., high withstand voltage) described below are properties common to the compound powder 10, the green body, and the cured product. The soft magnetic properties (e.g., high relative permeability) described below are also properties common to the compound powder 10, the green body, and the cured product. The mechanical strength (e.g., high bending strength) described below is a property of the cured product of the compound powder 10.
[0026] The compound powder 10 includes a plurality of large particles 5 having a particle diameter d of more than 500 μm. The particle diameter d may be rephrased as the maximum width (long diameter) of one particle. The content of the large particles 5 in the compound powder 10 is 40% by mass or more and 100% by mass or less. The compound powder 10 having a large particle 5 content of 40 mass% or more has better electrical insulation (voltage resistance) than the compound powder having a large particle 5 content of less than 40 mass%. Therefore, electrical short circuits and eddy current losses are suppressed in industrial products manufactured from the compound powder 10. Blocking (aggregation) of the compound powder 10 having a large particle 5 content of 40% by mass or more is easily suppressed compared to a compound powder having a large particle 5 content of less than 40% by mass. Therefore, blocking of the compound powder 10 accompanying transfer molding or compression molding of the compound powder 10 is suppressed, the compound powder 10 is easily fluidized, and poor appearance due to blocking is less likely to occur on the surface of the cured product of the compound powder 10. The content of the large particles 5 in the compound powder 10 may be preferably 60% by mass or more and 100% by mass or less, more preferably 80% by mass or more and 100% by mass or less, because this makes it easier to improve the electrical insulation of the compound powder 10. The compound powder 10 may be composed only of a plurality of large particles 5. In other words, the content of the large particles 5 in the compound powder 10 may be 100% by mass. As long as the content of the large particles 5 is 40% by mass or more, the compound powder 10 may further contain a plurality of small particles 7 having a particle diameter d of 500 μm or less in addition to the plurality of large particles 5. In other words, the content of the small particles 7 in the compound powder 10 is 0% by mass or more and 60% by mass or less.
[0027] At least a portion of the multiple large particles 5 may include at least one metal particle 1 constituting the metal powder and a resin composition covering the metal particle 1. The term "composite particle" described below means a particle including at least one metal particle 1 and a resin composition 3 covering the metal particle 1. As the amount of resin composition 3 covering the metal particles 1 increases, the particle size of the composite particles (the thickness of the resin composition 3 covering the metal particles 1) increases. As a result, the particle size of the composite particles increases, and large particles 5 with particle size d of more than 500 μm are likely to be formed. When the surface of the large particles 5 is made of the resin composition 3 having electrical insulation properties, the large particles 5 themselves have excellent electrical insulation properties, and the electrical insulation properties of the compound powder 10 containing a plurality of large particles 5 are also improved. As the number of large particles 5 increases (the particle size of each composite particle increases), the specific surface area of the compound powder 10 decreases, and contact and aggregation between multiple particles in the compound powder 10 is easily suppressed. In other words, as the number of large particles 5 increases (the particle size of each composite particle increases), blocking (aggregation) of the compound powder 10 is easily suppressed.
[0028] All of the large particles 5 contained in the compound powder 10 may be composite particles. Only a portion of the large particles 5 may be composite particles, and the remainder of the large particles 5 may be at least one of particles consisting of only the resin composition 3 and metal particles 1 not covered with the resin composition 3. When the compound powder 10 contains a plurality of small particles 7, some or all of the plurality of small particles 7 may be composite particles. For example, only some of the plurality of small particles 7 may be composite particles, and the remaining portion of the plurality of small particles 7 may be at least one of particles consisting of only the resin composition 3 and metal particles 1 not covered with the resin composition 3. All of the plurality of small particles 7 contained in the compound powder 10 may be metal particles 1 not covered with the resin composition 3. The smaller the particle size of the metal particles 1, the more easily the resin composition 3 peels off from the surface of the metal particles 1, and the less likely the large particles 5 are to be formed. Therefore, the plurality of small particles 7 are more likely to contain metal particles 1 not covered with the resin composition 3. One composite particle may include a plurality of metal particles 1 and a resin composition 3 covering the plurality of metal particles 1. The resin composition 3 contained in one composite particle may cover a part or the whole of the surface of the metal particle 1 contained in the composite particle. The resin composition 3 contained in one composite particle may directly cover the surface of the metal particle 1 contained in the composite particle. The resin composition 3 contained in one composite particle may indirectly cover the surface of the metal particle 1. For example, an insulating coating containing an inorganic compound (SiO2, etc.) may directly cover the surface of one metal particle 1, and the resin composition 3 may directly cover the surface of the insulating coating.
[0029] The upper limit of the particle size of the large particles 5 is not particularly limited. For example, the particle size of the large particles 5 may be greater than 500 μm and less than 4000 μm, greater than 500.1 μm and less than 4000.0 μm, greater than 500 μm and less than 2000 μm, or greater than 500.1 μm and less than 2000.0 μm. The average particle size or median diameter (D50) of the large particles 5 is not particularly limited. For example, the average particle size or median diameter of the large particles 5 may be greater than 500 μm and less than 4000 μm, greater than 500.1 μm and less than 4000.0 μm, greater than 500 μm and less than 2000 μm, or greater than 500.1 μm and less than 2000.0 μm. For example, the particle size of the large particles 5 may be calculated from the particle size distribution of the compound powder 10 based on the mass, volume, or number of the large particles 5. For example, the particle size distribution may be measured by a laser diffraction particle size distribution measuring device. For example, the particle size distribution may be calculated based on the measurement of the mass or volume of the large particles 5 by sieving. The shapes of the large particles 5 and the small particles 7 are not particularly limited. For example, the shapes of the large particles 5 and the small particles 7 may be spherical, approximately spherical, flat, or acicular.
[0030] The compound powder 10 may be fluidized by heating at a temperature lower than the thermosetting temperature of the resin composition 3, and the fluidized compound powder 10 may be molded. For example, the compound powder 10 is easily used for transfer molding. Transfer molding is a type of injection molding method. Transfer molding may be called pressure molding. Transfer molding may include a process of heating and fluidizing the compound powder 10 in a heating chamber, and a process of feeding (pressing) the fluidized compound powder 10 from the heating chamber into a mold through a casting runner. The molding method of the compound powder 10 is not limited to transfer molding. For example, the molding method of the compound powder 10 may be extrusion molding or compression molding (powder compaction molding).
[0031] The minimum melt viscosity of the compound powder 10 at 175°C may be 10 Pa·s or more and 250 Pa·s or less. Pa·s means Pascal seconds. When the minimum melt viscosity is within the above range, the heated compound powder 10 has excellent fluidity, so that the compound powder 10 flows easily through a thin runner without interruption (without containing air bubbles) and is easily filled into the space (cavity) in the mold without unevenness. As a result, a molded body and its hardened product with few defects such as poor appearance, voids, and burrs are easily produced by the above molding method. The minimum melt viscosity of the compound powder 10 at 175°C may be 21 Pa·s or more and 34 Pa·s or less.
[0032] The content of the metal powder in the compound powder 10 is not particularly limited. For example, the content of the metal powder in the compound powder 10 may be 94% by mass or more and 98% by mass or less. The content of the resin composition in the compound powder 10 may be 2% by mass or more and 6% by mass or less. When the content of the metal powder in the compound powder 10 is 94% by mass or more, the soft magnetic properties of the compound powder 10 are likely to be improved. When the content of the metal powder in the compound powder 10 is 98% by mass or less and the content of the resin composition 3 in the compound powder 10 is 2% by mass or more, the compound powder 10 is likely to include a plurality of large particles 5, the electrical insulation of the compound powder 10 is likely to be improved, and blocking of the compound powder 10 is likely to be suppressed. The content of the metal powder in the compound powder 10 may be 95.0% by mass or more and 95.2% by mass or less, and the content of the resin composition in the compound powder 10 may be 4.8% by mass or more and 5.0% by mass or less.
[0033] For example, the content of each of the metal powder and the resin composition 3 in the compound powder 10 may be specified by the following method based on the specific gravity of each of the compound powder 10, the metal powder, and the resin composition 3. The specific gravity (unit: no) may be the ratio of the density of each of the compound powder 10, the metal powder, and the resin composition 3 to the density of a standard substance (for example, the density of water at 4°C). For example, the specific gravity of each of the compound powder 10, the metal powder, and the resin composition 3 may be measured by a general method (such as an underwater displacement method) based on Archimedes' principle. The specific gravity of each of the metal powder and the resin composition 3 may be measured in advance before the production of the compound powder 10. The compound powder 10 may be separated into the metal powder and the resin composition 3 (an organic substance dissolved in an organic solvent) using an inert organic solvent that does not react with the metal powder and the resin composition 3, and the specific gravity of each of the metal powder and the resin composition 3 separated from each other may be measured. The specific gravity of the metal powder is S M The content of the metal powder in the compound powder 10 may be expressed as α% by mass. The specific gravity of the resin composition 3 may be expressed as S R The content of the resin composition 3 in the compound powder 10 may be expressed as (100-α) mass %. The specific gravity S of the compound powder 10 C may be expressed by the following formula 1. Based on the following formula 1, each measured specific gravity (S M ,S R , and S C ) the content α of metal powder in the compound powder 10 may be calculated. S C =[(S M ×α) + {S R ×(100-α)}] / 100 (1)
[0034] The compound powder 10 and its compact may be used as a raw material for the magnetic core of a coil. In other words, the hardened compound powder 10 may be the magnetic core of a coil. For example, specific industrial products (products including coils) manufactured using the compound powder 10 may be inductors, power supply modules, transformers, reactors, thyristor valves, noise filters (EMI filters), choke coils, rotors and yokes of motors, and solenoid cores (fixed iron cores) for solenoid valves incorporated in electronically controlled fuel injection devices of internal combustion engines.
[0035] The compound powder 10 can have both the electrical insulation required for an encapsulant for electronic devices and the soft magnetic properties (electromagnetic shielding ability) required for an electromagnetic shielding material. Therefore, the compound powder 10, its molded body, and its cured product may be an encapsulant that also serves as an electromagnetic shielding material. The compound powder 10, its molded body, and its cured product may be an encapsulant for electronic components or electrical devices. For example, the encapsulant that also serves as an electromagnetic shielding material may be an encapsulant (such as an underfill) for semiconductor packages such as IC packages and LSI packages.
[0036] (Specific examples of metal powder) The metal powder (multiple metal particles 1) may include multiple types of metal powders having different particle sizes. For example, the metal powder may include a first soft magnetic powder (multiple first soft magnetic particles) and a second soft magnetic powder (multiple second soft magnetic particles), and the particle size of the first soft magnetic powder may be larger than that of the second soft magnetic powder. For example, the average particle size of the first soft magnetic powder may be larger than that of the second soft magnetic powder. For example, the D50 (median diameter) of the first soft magnetic powder may be larger than that of the second soft magnetic powder. For example, the D90 of the first soft magnetic powder may be larger than that of the second soft magnetic powder. If the compound powder 10 includes only the first soft magnetic powder having a large particle size as the metal powder, gaps are likely to be formed between the adjacent first soft magnetic particles, and the filling rate of the metal powder in the compound powder 10 is difficult to increase. On the other hand, when the compound powder 10 contains the first soft magnetic powder and the second soft magnetic powder as the metal powder, the second soft magnetic particles smaller than the first soft magnetic particles are filled in the gaps between the first soft magnetic particles, and the filling rate of the metal powder in the compound powder 10 increases. In other words, the compound powder 10 contains the first soft magnetic powder and the second soft magnetic powder having different particle sizes, and therefore the specific gravity of the compound powder 10 increases. As a result, the soft magnetic properties improve. Furthermore, as the filling rate of the metal powder in the compound powder 10 increases, the hardened product of the compound powder 10 becomes dense, and the mechanical strength of the hardened product improves.
[0037] For example, the average particle size of the metal powder (multiple metal particles 1) may be 0.1 μm or more and 45 μm or less. For example, the average particle size of the first soft magnetic powder may be 11 μm or more and 45 μm or less. For example, the average particle size of the second soft magnetic powder may be 0.1 μm or more and 9.0 μm or less. When the average particle size of the first soft magnetic powder is within the above range and the average particle size of the second soft magnetic powder is also within the above range, the filling rate of the metal powder in the compound powder 10 is likely to increase, and the soft magnetic properties and mechanical strength are likely to be improved.
[0038] The average particle size, D50, and D90 of the metal powder may be calculated from a particle size distribution based on the number, volume, or mass of the first soft magnetic particles constituting the first soft magnetic powder. The average particle size, D50, and D90 of the first soft magnetic powder may be calculated from a particle size distribution based on the number, volume, or mass of the first soft magnetic particles constituting the first soft magnetic powder. The average particle size, D50, and D90 of the second soft magnetic powder may be calculated from a particle size distribution based on the number, volume, or mass of the second soft magnetic particles constituting the second soft magnetic powder. Each particle size distribution may be measured by a laser diffraction particle size distribution measuring device. Each particle size distribution may be calculated based on the measurement of the mass or volume of each soft magnetic particle by sieving. The shapes of the metal powder (metal particles 1), the first soft magnetic particles, and the second soft magnetic particles are not particularly limited. For example, the shape of each of the metal powder (metal particles 1), the first soft magnetic particles, and the second soft magnetic particles may be spherical, approximately spherical, flat, or acicular.
[0039] The mass of the first soft magnetic powder may be represented as M1, and the mass of the second soft magnetic powder may be represented as M2. M1 / (M1+M2) may be 0.70 or more and 0.95 or less, and M2 / (M1+M2) may be 0.05 or more and 0.30 or less. When M1 / (M1+M2) and M2 / (M1+M2) are within the above ranges, the second soft magnetic particles smaller than the first soft magnetic particles are easily filled into the gaps between the first soft magnetic particles, and the filling rate of the metal powder in the compound powder 10 (specific gravity of the compound powder 10) is easily increased. As a result, the soft magnetic properties and mechanical strength are easily improved.
[0040] The compound powder 10 may further include a non-metallic filler in addition to the metal powder. For example, the compound powder 10 may include a filler (particulate filler) made of silica (SiO2) as the non-metallic filler. The particle size of the non-metallic filler may be approximately or completely equal to the particle size of the metal powder.
[0041] As long as the metal powder is a soft magnetic material, the composition of the metal powder (each of the plurality of metal particles 1) is not particularly limited. For example, the metal powder may contain iron. In addition to iron, the metal powder may further contain at least one metal element selected from the group consisting of base metal elements, precious metal elements, transition metal elements, and rare earth elements. For example, the metal element other than iron contained in the metal powder may be at least one element selected from the group consisting of copper (Cu), titanium (Ti), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), tin (Sn), chromium (Cr), barium (Ba), strontium (Sr), lead (Pb), and silver (Ag). The metal powder may contain a nonmetal element in addition to a metal element. For example, the nonmetal element contained in the metal powder may be at least one element selected from the group consisting of oxygen (O), beryllium (Be), phosphorus (P), boron (B), and silicon (Si).
[0042] The metal powder may contain at least one metal selected from the group consisting of pure iron and an alloy containing iron (iron-based alloy). The metal powder may consist of only pure iron. The metal powder may consist of only an iron-based alloy. The metal powder may consist of only pure iron and an iron-based alloy. For example, the iron-based alloy contained in the metal powder may be at least one alloy selected from the group consisting of Fe-Cr-Si alloy, Fe-Cr alloy, Fe-Si alloy, Fe-Si-Al alloy, Fe-Ni alloy, Fe-Cu-Ni alloy, Fe-Co alloy, and Fe-Ni-Cr alloy. The iron or iron-based alloy contained in the metal powder may be crystalline or amorphous. The metal powder may contain a plurality of types of metal powders having different compositions.
[0043] A part or all of the metal particles 1 constituting the metal powder may be covered with an insulating coating. A part or all of the surface of each metal particle 1 may be covered with an insulating coating. By covering the metal powder with an insulating coating, the electrical insulation of the compound powder 10 is improved. When the insulating coating contains glass, the surface of the insulating coating is likely to be smooth, and friction between the multiple metal particles 1 is likely to be suppressed. As a result, blocking of the compound powder 10 is likely to be suppressed, and the fluidity of the compound powder 10 is likely to be improved.
[0044] For example, the insulating coating may include at least one component selected from the group consisting of glass, phosphoric acid (phosphate), silica (SiO2), iron oxide (Fe2O3), and chromium oxide (Cr2O3). For example, the glass may include at least one element selected from the group consisting of oxygen (O), boron (B), sodium (Na), and aluminum (Al) in addition to silicon (Si). For example, the glass may include at least one component selected from silicate glass (silicate), phosphosilicate glass (phosphosilicate), and borosilicate glass (borosilicate). The composition of the insulating coating may be measured by at least one analytical method selected from photoelectron spectroscopy (XPS) and energy dispersive X-ray analysis (EDX). The insulating coating may be formed by a wet method using an alkoxysilane solution or the like, or a dry method such as mechanofusion. For example, the thickness of the insulating coating may be 10 nm or more and 200 nm or less. The thickness of the insulating coating may be measured on the cross-section of the metal particle 1 by transmission electron microscopy (TEM) and EDX.
[0045] (Specific examples of resin compositions) The resin composition 3 is the remaining portion (non-volatile component) of the compound powder 10 excluding the metal powder and the organic solvent. The resin composition contains at least a thermosetting resin. In addition to the thermosetting resin, the resin composition 3 may further contain at least one component selected from the group consisting of a curing agent, a curing accelerator (curing catalyst), a coupling agent, a wax (mold release agent), and a flame retardant. Specific examples of each component are as follows.
[0046] The thermosetting resin contained in the resin composition 3 may be at least one resin selected from the group consisting of epoxy resin, phenol resin, bismaleimide resin, polyimide resin, and polyamideimide resin. The resin composition may further contain other resins (e.g., thermoplastic resins) in addition to the thermosetting resin. For example, the resin composition may further contain at least one other resin selected from the group consisting of polyphenylene sulfide resin, acrylic resin, methacrylic resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyethylene terephthalate, and silicone resin.
[0047] <Epoxy resin and hardener> The epoxy resin may be a biphenyl type epoxy resin, a stilbene type epoxy resin, a diphenylmethane type epoxy resin, a sulfur atom-containing type epoxy resin, a novolac type epoxy resin, a dicyclopentadiene type epoxy resin, a salicylaldehyde type epoxy resin, a copolymer type epoxy resin of naphthols and phenols, an epoxidized product of an aralkyl type phenolic resin, a bisphenol type epoxy resin, a glycidyl ether type epoxy resin of alcohols, a glycidyl ether type epoxy resin of a paraxylylene modified phenolic resin and / or a metaxylylene modified phenolic resin, a glycidyl ether type epoxy resin of a terpene modified phenolic resin, or a combination thereof. and at least one resin selected from the group consisting of glycidyl ether type epoxy resins of polycyclic aromatic ring-modified phenolic resins, glycidyl ether type epoxy resins of naphthalene ring-containing phenolic resins, glycidyl ester type epoxy resins, glycidyl or methylglycidyl type epoxy resins, alicyclic type epoxy resins, halogenated phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, hydroquinone type epoxy resins, trimethylolpropane type epoxy resins, and linear aliphatic epoxy resins obtained by oxidizing an olefin bond with a peracid such as peracetic acid.
[0048] At least a part of the epoxy resin may be a naphthalene type epoxy resin having a naphthalene structure. The naphthalene type epoxy resin is solid at room temperature. When the compound powder 10 contains a naphthalene type epoxy resin, a product (a cured product of the compound powder 10) manufactured from the compound powder 10 tends to have high mechanical strength at room temperature and high temperature. The naphthalene type epoxy resin may be at least one resin selected from the group consisting of a naphthalene diepoxy compound, a naphthylene ether type epoxy resin, a naphthalene novolac type epoxy resin, a methylene bond dimer of a naphthalene diepoxy compound, and a methylene bond of a naphthalene monoepoxy compound and a naphthalene diepoxy compound. The epoxy resin may include a bifunctional epoxy resin. For example, the bifunctional epoxy resin may be at least one resin selected from an α-naphthol type epoxy resin and a β-naphthol type epoxy resin.
[0049] The epoxy resin may include at least one of a trifunctional epoxy resin and a tetrafunctional epoxy resin. The above-mentioned naphthalene type epoxy resin may be at least one of a trifunctional epoxy resin and a tetrafunctional epoxy resin. The trifunctional epoxy resin is an epoxy resin composed of a structural unit having three epoxy groups. The tetrafunctional epoxy resin is an epoxy resin composed of a structural unit having four epoxy groups. When the epoxy resin includes at least one of a trifunctional epoxy resin and a tetrafunctional epoxy resin, the epoxy resins are three-dimensionally crosslinked with each other during the thermal curing of the compound powder 10, forming a strong crosslinked network. As a result, the movement of the epoxy resin in the cured product of the compound powder 10 is easily suppressed at high temperatures. In other words, the glass transition temperature of each of the trifunctional epoxy resin and the tetrafunctional epoxy resin is higher than the glass transition temperature of the bifunctional epoxy resin. Therefore, when the epoxy resin contains at least one of a trifunctional epoxy resin and a tetrafunctional epoxy resin, the cured material of the compound powder 10 (a product produced from the compound powder 10) tends to have high mechanical strength at high temperatures.
[0050] The compound powder 10 may contain one of the above epoxy resins. The compound powder 10 may contain a plurality of the above epoxy resins.
[0051] Curing agents are classified into curing agents that cure epoxy resins in the range from low temperature to room temperature, and heat-curing curing agents that cure epoxy resins by heating. For example, curing agents that cure epoxy resins in the range from low temperature to room temperature include aliphatic polyamines, polyaminoamides, and polymercaptans. For example, heat-curing curing agents include aromatic polyamines, acid anhydrides, phenolic resins, phenolic novolac resins, and dicyandiamide (DICY). From the viewpoint of improving the heat resistance (mechanical strength at high temperature) of the cured product of the compound powder 10, the curing agent may be preferably a heat-curing curing agent, more preferably a phenolic resin, and even more preferably a phenolic novolac resin.
[0052] A part or all of the curing agent may be a phenolic resin. For example, the phenolic resin may be at least one resin selected from the group consisting of aralkyl type phenolic resin, dicyclopentadiene type phenolic resin, salicylaldehyde type phenolic resin, novolac type phenolic resin, copolymer type phenolic resin of benzaldehyde type phenol and aralkyl type phenol, paraxylylene and / or metaxylylene modified phenolic resin, melamine modified phenolic resin, terpene modified phenolic resin, dicyclopentadiene type naphthol resin, cyclopentadiene modified phenolic resin, polycyclic aromatic ring modified phenolic resin, biphenyl type phenolic resin, and triphenylmethane type phenolic resin. The phenolic resin may be a copolymer composed of two or more of the above phenolic resins.
[0053] The phenol novolac resin may be a resin obtained by condensing or co-condensing phenols and / or naphthols with aldehydes under an acid catalyst. The phenols constituting the phenol novolac resin may be at least one selected from the group consisting of phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol. The naphthols constituting the phenol novolac resin may be at least one selected from the group consisting of α-naphthol, β-naphthol, and dihydroxynaphthalene. The aldehydes constituting the phenol novolac resin may be at least one selected from the group consisting of formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde.
[0054] The curing agent may be a compound having two phenolic hydroxyl groups in one molecule. For example, the compound having two phenolic hydroxyl groups in one molecule may be at least one compound selected from the group consisting of resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenol.
[0055] The compound powder 10 may contain one of the above phenol resins as a hardener. The compound powder 10 may contain a plurality of the above phenol resins as a hardener.
[0056] The ratio of the hydroxyl group equivalent of the phenol resin to the epoxy equivalent of the epoxy resin may be 0.5 or more and 1.5 or less. In other words, the ratio of the active group (phenolic OH group) in the phenol resin that reacts with the epoxy group in the epoxy resin may be 0.5 or more and 1.5 or less equivalents per equivalent of epoxy group in the epoxy resin.
[0057] <Curing accelerator> The curing accelerator (curing catalyst) is not limited as long as it is a composition that reacts with the epoxy resin to accelerate the curing of the epoxy resin. For example, the curing accelerator may be a urea compound. The curing accelerator may be an imidazole such as an alkyl group-substituted imidazole or benzimidazole. The curing accelerator may be a phosphorus-based curing accelerator. The compound powder 10 may include one type of curing accelerator. The compound powder 10 may include multiple types of curing accelerators.
[0058] The amount of the curing accelerator is not particularly limited. From the viewpoint of improving the curing property and fluidity of the epoxy resin when absorbing moisture, the amount of the curing accelerator may be 0.1 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the epoxy resin. The content of the curing accelerator may be 0.001 parts by mass or more and 5 parts by mass or less with respect to the total mass of the epoxy resin and the curing agent (e.g., phenolic resin).
[0059] <Coupling Agent> The coupling agent may be a coupling agent that reacts with a glycidyl group of a resin composition such as an epoxy resin. The coupling agent improves the adhesion between the metal powder and the resin composition 3, and improves the mechanical strength of the cured product of the compound powder 10. The coupling agent that reacts with the glycidyl group may be a silane-based compound (silane coupling agent). For example, the silane coupling agent may be at least one coupling agent selected from the group consisting of epoxy silane, mercapto silane, amino silane, alkyl silane, ureido silane, acid anhydride silane, and vinyl silane. The compound powder 10 may contain one of the above coupling agents. The compound powder 10 may contain multiple types of the above coupling agents.
[0060] <Wax> The compound powder 10 may contain wax. Wax may be referred to as a lubricant or a mold release agent. When the compound powder 10 contains wax, the fluidity and moldability of the compound powder 10 are improved, and the mold release property of the compound powder 10 is improved. As a result, the accuracy of the shape and dimensions of the product (hardened product of the compound powder 10) manufactured from the compound powder 10 is improved, and structural defects of the product are easily suppressed. For example, the wax may be at least one compound selected from the group consisting of saturated fatty acids, saturated fatty acid salts, and saturated fatty acid esters. The wax may be a synthetic wax. The compound powder 10 may contain one type of wax among the above. The compound powder 10 may contain multiple types of wax among the above.
[0061] <Flame retardants> The compound powder 10 may contain a flame retardant. For example, the flame retardant may be at least one compound selected from the group consisting of bromine-based flame retardants, phosphorus-based flame retardants, hydrated metal powder-based flame retardants, silicone-based flame retardants, nitrogen-containing compounds, hindered amine compounds, organometallic compounds, and aromatic engineering plastics. The compound powder 10 may contain one of the above flame retardants, or may contain multiple of the above flame retardants.
[0062] (Method of manufacturing compound powder) The method for producing the compound powder includes a step (step A) of preparing a mixed powder containing a metal powder and a resin composition, and a step (step B) of obtaining a compound powder containing a plurality of large particles by classifying the mixed powder.
[0063] <Process A> For example, in step A, a mixed powder may be obtained by kneading the metal powder and each component constituting the resin composition while heating. A lump of the mixed powder (agglomerated mixed powder) may be obtained by heating and kneading the metal powder and the resin composition, and the mixed powder may be obtained by pulverizing the lump of the mixed powder.
[0064] For example, the kneading means for the metal powder and the resin composition may be a kneader, a roll, or a stirrer. By heating and mixing the metal powder and the resin composition, the resin composition may cover a part or the whole of the surface of each metal particle constituting the metal powder. By heating and mixing the metal powder and the resin composition, a part or the whole of the resin composition may become a semi-cured product.
[0065] The metal powder and all the components constituting the resin composition may be kneaded together. A mixture of the metal powder and the coupling agent may be prepared in advance, and this mixture may be kneaded with other components of the resin composition. A mixture of each component of the resin composition except the curing accelerator and the metal powder may be prepared in advance, and this mixture may be kneaded with the curing accelerator. A mixture of each component of the resin composition except the wax and the metal powder may be prepared in advance, and this mixture may be kneaded with the wax.
[0066] The kneading time depends on the kneading means, the volume of the kneading means, and the production amount of the compound powder. The kneading time is not limited. For example, the kneading time may be 1 minute or more and 20 minutes or less. For example, the temperature (heating temperature) of the metal powder and the resin composition during kneading may be lower than the thermosetting temperature of the thermosetting resin. The heating temperature may be a temperature at which a semi-cured product of the thermosetting resin (a B-stage resin composition) is produced and the production of a cured product of the thermosetting resin (a C-stage resin composition) is suppressed. The heating temperature may be a temperature lower than the activation temperature of the curing accelerator. For example, the heating temperature may be 50°C or more and 150°C or less.
[0067] The method for preparing the mixed powder is not limited to the above method. For example, the mixture may be obtained by kneading the metal powder, the resin composition, and the organic solvent while heating, and the mixed powder may be obtained by drying (and pulverizing) the mixture. When the organic solvent in which the resin composition is dissolved contacts the surface of the metal particles, the metal particles are easily covered with the resin composition, and a mixed powder containing large particles is easily obtained. For the same reason, the mixed liquid may be obtained by mixing the metal powder and the resin composition in an organic solvent, and the mixed powder may be obtained by drying (and pulverizing) the mixed liquid. For example, the organic solvent may be at least one solvent selected from the group consisting of acetone, methyl ethyl ketone (2-butanone), methyl isobutyl ketone (4-methyl-2-pentanone), benzene, toluene, xylene, and N-methyl-2-pyrrolidone (NMP).
[0068] <Process B> In step B, the mixed powder is classified to obtain a compound powder containing a plurality of large particles having a particle size larger than 500 μm. For example, the mixed powder is classified using a sieve with an opening of 500 μm to separate the large particles from the mixed powder. That is, the large particles in the mixed powder do not pass through the sieve with an opening of 500 μm, and the small particles in the mixed powder pass through the sieve. Only the large particles obtained by classifying the mixed powder may be used for the compound powder. The large particles and the small particles may be mixed after classification to obtain a compound powder having a large particle content of 40 mass% or more.
[0069] In the following, the mass (unit: g) of the mixed powder before classification is M M The total mass of the large particles obtained by classification using a sieve with a mesh size of 500 μm is expressed as M L It is expressed as: M L can be said to be the sum of the masses of the multiple large particles in the mixed powder before classification. The sum of the masses of the multiple small particles in the mixed powder before classification is M S It is expressed as follows. Naturally, M M is M L +M S is equal to. The mesh size of the sieve used to classify the mixed powder is not limited to 500 μm. A plurality of sieves with different mesh sizes may be used to classify the mixed powder. For example, if the mesh size of any sieve X is any positive real number x (unit: μm) and x is less than 500 μm, a powder X' having a particle size larger than x μm is separated from the mixed powder by classifying the mixed powder using the sieve X. In other words, particles having a particle size larger than x μm do not pass through the sieve X, and small particles having a particle size of x μm or less pass through the sieve. The powder X' having a particle size larger than x μm includes small particles having a particle size larger than x μm and 500 μm or less, and large particles having a particle size larger than 500 μm. The mass of the powder X' having a particle size larger than x μm is M X Powder X' contains all the large particles from the mixed powder. Therefore, the total mass of the large particles in powder X' is expressed as M L and the content of large particles in powder X' is {(M L / M X )×100} mass%. L / M X )×100} is 40 mass % or more, the powder X' itself having a particle size larger than x μm can be used as the compound powder according to this embodiment. The particle size distribution of the mixed powder before classification may be measured in advance. The opening x of the sieve X is selected or adjusted in advance based on the particle size distribution of the mixed powder, so that {(M L / M X )×100} can be freely controlled within a range of 40 mass % or more and less than 100 mass %. For example, the opening x of the sieve X may be 75 μm or more and 300 μm or less. As the opening x of the sieve X increases, the content of the multiple small particles in the powder X' decreases, and {(M L / M X )×100} increases.
[0070] The method for producing the compound powder is not limited to the above method. For example, a compound powder having a large particle content of 40% by mass or more may be produced by a pulverization step in which the mixed powder or lumps of mixed powder obtained in the above step A are pulverized. By adjusting the various operating conditions of the pulverization step and selecting the pulverization means, the degree of pulverization of the mixed powder or lumps of mixed powder can be freely adjusted, and the particle size and particle size distribution of the compound powder obtained by the pulverization step can be freely controlled. In other words, by adjusting the various operating conditions of the pulverization step and selecting the pulverization means, the formation of small particles from the mixed powder or lumps of mixed powder is suppressed, and a compound powder having a large particle content of 40% by mass or more can be obtained. For example, a compound powder having a large particle content of 40% by mass or more may be produced by a blending step in which multiple types of compound powders differing in particle size or particle size distribution are mixed. When at least one type of compound powder among multiple types of compound powders having different particle size distributions contains multiple large particles, and the particle size or particle size distribution of each of the multiple types of compound powders is measured in advance, a compound powder having a large particle content of 40% by mass or more is obtained by adjusting the mixing ratio (e.g., mass ratio or volume ratio) of the multiple types of compound powders in the blending step. For example, a large powder consisting only of multiple large particles and a small powder consisting only of multiple small particles may be obtained by the above step B (classification of the mixed powder). A compound powder having a large particle content of 40% by mass or more is obtained by mixing 40 parts by mass or more of the large powder and 60 parts by mass or less of the small powder.
[0071] (Method of manufacturing molded product and cured product) A molded body is obtained by molding the above-mentioned compound powder. By heat treatment of the molded body (thermal curing of the resin composition in the molded body), a plurality of metal particles are firmly bound to each other by the cured product of the resin composition, and a cured product of the compound powder is obtained. For example, the molding method of the compound powder may be transfer molding, extrusion molding, or compression molding (powder compaction). The dimensions and shape of the mold used for molding the compound powder may be selected according to the industrial product manufactured using the compound powder. The heat treatment temperature of the molded body may be a temperature at which the resin composition in the molded body is sufficiently cured, and may be equal to or higher than the activation temperature of the curing accelerator. For example, the heat treatment temperature may be 100°C or higher and 300°C or lower. For example, the heat treatment time may be several minutes or more and 10 hours or less. In order to suppress oxidation of the metal powder in the molded body, the heat treatment of the molded body may be performed under an inert atmosphere.
[0072] (Method of analyzing composition) The composition of the compound powder itself used in the manufacture of each of the molded body and the cured body may be analyzed retrospectively by analyzing samples obtained by pulverizing each of the molded body and the cured body. The sample may be dissolved in an organic solvent, and the metal powder may be separated from the resin composition 3 dissolved in the organic solvent. The metal powder and the resin composition 3 separated from each other may be analyzed individually. Even when the unused compound powder itself is directly analyzed, the metal powder and the resin composition separated from each other by the above method may be analyzed individually. For example, the metal powder may be analyzed and characterized by one or more analytical methods selected from the group consisting of X-ray Fluorescence (XRF), Inductively Coupled Plasma (ICP) Emission Spectroscopy, X-ray Photoelectron Spectroscopy (XPS), Energy Dispersive X-ray Spectroscopy (EDS or EDX), and Mass Spectrometry (MS). For example, each component (such as a thermosetting resin) constituting the resin composition may be analyzed and identified by one or more analytical methods selected from the group consisting of infrared spectroscopy (IR), nuclear magnetic resonance (NMR), gas chromatography (GC), high performance liquid chromatography (HPLC), and mass spectrometry.
[0073] The present invention is not necessarily limited to the above-described embodiment. Various modifications of the present invention are possible without departing from the spirit of the present invention, and these modifications are also included in the present invention. EXAMPLES
[0074] The present invention will be described in detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.
[0075] Example 1 <Step A: Preparation of mixed powder> As the metal powder, a mixture of a first soft magnetic powder and a second soft magnetic powder was used. The first soft magnetic powder used was 9A4-II 053C03 manufactured by Epson Atmix Corp. The first soft magnetic powder had an average particle size of 24 μm and was substantially uniform. The first soft magnetic powder was a powder of a soft magnetic alloy made of Fe and Si, and did not contain Cr. As the second soft magnetic powder, "SAP-2C" manufactured by Shinto Kogyo Co., Ltd. was used. "SAP-2C" was a powder of a soft magnetic alloy made of Fe, Cr and Si. The average particle size of the second soft magnetic powder was 2 μm and was approximately uniform. The content of the first soft magnetic powder in the metal powder was 82 mass %. The content of the second soft magnetic powder in the metal powder was 18 mass %.
[0076] The components constituting the resin composition were an epoxy resin, a curing agent, a curing accelerator (catalyst), a coupling agent, and a wax (mold release agent).
[0077] As the epoxy resin, "NC-3000" manufactured by Nippon Kayaku Co., Ltd. and "TECHMORE VG-3101L" manufactured by Printec Co., Ltd. were used. "NC-3000" is a biphenyl aralkyl type epoxy resin. The mass of "NC-3000" was 60 g. "TECHMORE VG3101L" is a trifunctional epoxy resin and is a derivative of 1-[α-methyl-α-(4-hydroxyphenyl)ethyl]-4-[α,α-bis(4-hydroxyphenyl)ethyl]benzene. The mass of "TECHMORE VG3101L" was 40g.
[0078] The hardener used was "HF-3M" manufactured by UBE Corporation (formerly Meiwa Kasei Co., Ltd.). "HF-3M" is a phenolic resin. The mass of "HF-3M" was 43.2g.
[0079] As the curing accelerator (catalyst), "U-CAT3512T" manufactured by San-Apro Co., Ltd. was used. "U-CAT3512T" is an aromatic dimethylurea. The mass of "U-CAT3512T" was 5.9g.
[0080] As the coupling agents, "KBM-803" and "KBM-5803" manufactured by Shin-Etsu Chemical Co., Ltd. were used. "KBM-803" is 3-mercaptopropyltrimethoxysilane. The mass of "KBM-803" was 1.9 g. "KBM-5803" is 8-methacryloxyoctyltrimethoxysilane. The mass of "KBM-5803" was 1.9 g.
[0081] The wax (release agent) used was "Licowax OP" manufactured by Clariant Chemicals Co., Ltd. "Licowax OP" is a montanic acid ester partially saponified with calcium hydroxide. The mass of "Licowax OP" was 2.0 g.
[0082] The metal powder and all of the components of the resin composition were kneaded while being heated to obtain a mixed powder. The temperature of the raw materials during kneading was a maximum of 130°C. The content of the metal powder in the mixed powder was adjusted to 95.5% by mass. In other words, the content of the resin composition in the mixed powder was adjusted to 4.5% by mass.
[0083] <Step B: Classification of mixed powder> The compound powder of Example 1 was separated from the mixed powder by classifying the mixed powder using a sieve with a mesh size of 75 μm. Only the powder of the mixed powder that did not pass through the sieve was used as the compound powder of Example 1. In other words, the compound powder of Example 1 was a powder with a particle size larger than 75 μm. The mass M of the compound powder Y (Unit: g) was measured. Mass M Y is the mass M of the powder X' described above X is equivalent to.
[0084] <Large particle content in compound powder> By classifying the compound powder using a sieve with a mesh size of 500 μm, several large particles with a particle size larger than 500 μm were separated from the compound powder. The total mass of the large particles separated from the compound powder, M L was measured. The content of large particles in the compound powder is {(M L / M Y )×100} mass %. The content of large particles in the compound powder of Example 1 is shown in Table 1 below. The content of small particles in the compound powder is [{(M Y -M L ) / M Y}×100] mass %. The content of the small particles in the compound powder of Example 1 is shown in Table 1 below.
[0085] <Specific gravity of compound powder and metal powder content in compound powder> The specific gravity of the compound powder was measured. The specific gravity of the compound powder of Example 1 is shown in Table 1 below. The content (filling rate) of the metal powder in the compound powder was calculated by the above-mentioned calculation method based on the specific gravity. The content of the metal powder in the compound powder of Example 1 is shown in Table 1 below.
[0086] <Dielectric strength> Test specimens were obtained by transfer molding of the compound powder at 175°C and post-curing (heating at 175°C for 5.5 hours) following transfer molding. The pressure applied to the compound powder during transfer molding was 13.5 MPa. The shape of the test specimen was a disk. The dimensions of the test specimen were 50 mm in diameter and 0.4 mm in thickness. In the following tests, a voltage was applied between a pair of electrodes sandwiching a test specimen using a source meter. The pair of electrodes was made of stainless steel. The end face of the positive electrode of the pair of electrodes was a circle with a diameter of 10 mm. The negative electrode of the pair of electrodes was a plate with a flat surface. In order to reduce the minute gap formed between the test specimen and the negative electrode, the surface of the negative electrode was covered with a sheet made of conductive rubber. The test specimen was placed on the sheet. In other words, the test specimen was in close contact with the surface of the negative electrode via the sheet. The end face of the positive electrode was in direct contact with the circular surface of the test specimen. The current in the test specimen was continuously measured while the DC voltage was continuously increased. The voltage (breakdown voltage) was read when the current passing through the test specimen exceeded 10 mA. The above test was repeated a total of 14 times in the same manner except for the position of the positive electrode. The median value of the breakdown voltage read in the 14 tests is defined as the withstand voltage (unit: V / mm) of the test specimen. A high-voltage dielectric property evaluation device manufactured by Yamayo Test Instruments Co., Ltd. was used as the source meter. A high withstand voltage means that the compound powder has excellent electrical insulation. For example, the withstand voltage is preferably 500 V / mm or more, and more preferably 550 V / mm or more. The withstand voltage of Example 1 is shown in Table 1 below.
[0087] <Blocking test> 100 g of compound powder was placed in a disposable cup. The volume of the disposable cup was 300 ml. A load of 300 gf was applied uniformly to the flat surface of the compound powder in the disposable cup. In other words, the compound powder in the disposable cup was uniformly compressed with a load of 300 gf. The mass of the compressed compound powder was M TOTAL In other words, M TOTAL is 100g. The compressed compound powder was classified using a sieve with a mesh size of 2 mm. The mass of the powder that passed through the sieve was M PASS The passing rate is expressed as {(M PASS / M TOTAL )×100}% by mass. The more the compound powder aggregates due to compression, the more difficult it becomes for the compound powder to pass through the sieve, and the lower the passing rate. By suppressing the blocking (aggregation) of the compound powder that accompanies compression of the compound powder, the compound powder becomes more likely to pass through the sieve, and the passing rate increases. In other words, a high passing rate is preferable. For example, the passing rate is preferably 50% or more. M in Example 1 PASS was measured. M PASS The weight of the powder was 100 g, and the passing rate was 100 mass %. In other words, all of the compressed compound powder passed through the sieve.
[0088] <Spiral Flow> The compound powder was placed in a transfer molding machine equipped with a mold. The spiral flow (unit: cm) of the compound powder was measured at a mold temperature of 175°C, an injection pressure of 6.9 MPa, and a molding time of 120 seconds. The spiral flow is the length of the compound powder flowing in the groove formed in the mold. In other words, the spiral flow is the flow distance of the softened or liquefied compound powder. The shape of the groove through which the compound powder flows is a spiral curve (Archimedes' spiral). The easier the compound powder flows, the larger the spiral flow. As the transfer molding machine, a 100KN transfer molding machine (PZ-10 type) manufactured by Kodaira Seisakusho Co., Ltd. was used. As the mold, a mold conforming to ASTM D3123 was used. It is preferable that the spiral flow is 100 cm or more. The spiral flow of Example 1 is shown in Table 1 below.
[0089] <Gel time> The gel time (gelation time) of the compound powder was measured at 175°C. A CURELASTOMETER manufactured by ENEOS Material Corporation (formerly JSR Corporation) was used as a gel time measuring device (vulcanization tester). The gel time (unit: seconds) of Example 1 is shown in Table 1 below.
[0090] <Minimum melt viscosity> The minimum melt viscosity (unit: Pa s) of the compound powder at 175°C was measured using a viscometer. The viscometer used was a CFT-100 (flow tester) manufactured by Shimadzu Corporation. The minimum melt viscosity of Example 1 is shown in Table 1 below.
[0091] (Examples 2 to 4 and Comparative Example 1) The mesh size of the sieve used in step B of each of Examples 2 to 4 is shown in the following Table 1. The compound powders of each of Examples 2 to 4 were produced in the same manner as in Example 1, except for the mesh size of the sieve used to classify the mixed powder. Step B of Comparative Example 1 was not performed. In other words, the mixed powder before classification was used as the compound powder of Comparative Example 1. Various measurements were carried out using the compound powders of Examples 2 to 4 and Comparative Example 1 in the same manner as in Example 1. The results of the various measurements of Examples 2 to 4 and Comparative Example 1 are shown in Table 1 below.
[0092] [Table 1] [Explanation of symbols]
[0093] 1...metal particles (metal powder), 3...resin composition, 5...large particles, 7...small particles, 10...compound powder.
Claims
1. A compound powder comprising a metal powder and a resin composition, The metal powder is a soft magnetic material, The resin composition includes a thermosetting resin, The compound powder includes a plurality of large particles having a particle size of more than 500 μm, The content of the large particles in the compound powder is 40% by mass or more and 100% by mass or less. Compound powder.
2. At least a portion of the plurality of large particles At least one metal particle constituting the metal powder; The resin composition covering the metal particles; Including, The compound powder according to claim 1.
3. The minimum melt viscosity of the compound powder at 175°C is 10 Pa·s or more and 250 Pa·s or less; The compound powder according to claim 1.
4. The content of the metal powder in the compound powder is 94% by mass or more and 98% by mass or less. The compound powder according to claim 1.
5. The resin composition further contains at least one component selected from the group consisting of a curing agent, a curing accelerator, a coupling agent, and a wax. The compound powder according to claim 1.
6. Used in the magnetic core of coils, The compound powder according to claim 1.
7. It is a sealing material, The compound powder according to claim 1.
8. A molded body comprising the compound powder according to claim 1.
9. A hardened product of the compound powder according to claim 1.
10. A method for producing the compound powder according to claim 1, comprising: preparing a mixed powder containing the metal powder and the resin composition; obtaining the compound powder containing the plurality of large particles by classifying the mixed powder; Equipped with Manufacturing method of compound powder.
Citation Information
Patent Citations
Winding inductor and its manufacturing method
JP2008277374A